Decoding the Virtual 2D Map of the Chloroplast Proteomes - Tapan Kumar Mohanta; Yugal Kishore Mohanta; Ahmed Al-Harrasi (Biological Procedures Online, 2022)
Abstract Background The chloroplast is a semi-autonomous organelle having its own genome and corresponding proteome. Although chloroplast genomes have been reported, no reports exist on their corresponding proteomes. Therefore, a proteome-wide analysis of the chloroplast proteomes of 2893 species was conducted, and a virtual 2D map was constructed. Results The resulting virtual 2D map of the chloroplast proteome exhibited a bimodal distribution. The molecular mass of the chloroplast proteome ranged from 0.448 to 616.334 kDa, and the isoelectric point (pI) ranged from 2.854 to 12.954. Chloroplast proteomes were dominated by basic pI proteins with an average pI of 7.852. The molecular weight and isoelectric point of chloroplast proteome were found to show bimodal distribution. Leu was the most abundant and Cys the least abundant amino acid in the chloroplast proteome. Notably, Trp amino acid was absent in the chloroplast protein sequences of Pilostyles aethiopica. In addition, Selenocysteine (Sec) and Pyrrolysine (Pyl) amino acids were also found to be lacking in the chloroplast proteomes. Conclusion The virtual 2D map and amino acid composition of chloroplast proteome will enable the researchers to understand the biochemistry of chloroplast protein in detail. Further, the amino acid composition of the chloroplast proteome will also allow us to understand the codon usage bias. The codon usage bias and amino acid usage bias of chloroplast will be crucial to understanding their relationship.